Productivity model and experiment of field crop spraying by plant protection unmanned aircraft - Qin, Weicai; Chen, Panyang; Wang, Baokun (Frontiers in Plant Science, 2023)
Traditional agricultural production needs a lot of manpower and material resources, while the ef-ficiency of agricultural production is low; The successful development of plant protection UAV has changed the operation mode of traditional agricultural production, which not only saves human, material and financial resources, but also significantly improves production efficiency. In order to summarize the process of improving the productivity of plant protection UAVs. The paper estab-lishes a productivity calculation model of UAV based on the time composition of UAV agricultural plant protection process, including spraying time, turning time, replenishment time and transfer time. the time required for the application process of unmanned aircraft is counted through years of tracking the application process of eight different plant protection unmanned aircraft. On this basis, the plot lengths of 100, 300, 500, 700, 1000, 1500, 2000, 2500, 3000 and 3500 are set respectively to calculate the theoretical productivity. The results show that the productivity of different types of plant protection UAVs increases with the increase of plot length in the range of 100 – 1500m, but when the plot length reaches a certain value, the productivity growth rate slows down or even decreases slightly. At the same time, based on the working area per 10000 mu, the recommended plot length and the number of configured models for different models are recommended. If the plant protection UAV is distinguished by electric and oil power, In recent years, the time utilization rate of electric plant protection UAVs is 72.7%, and the labor productivity is 56.4 mu / person·h. The time utilization rate of the heavy load oil-powered plant protection unmanned aircraft is 86%, and the labor productivity is 63.5 mu / person·h. This study can provide support for plant protection un-manned aircraft enterprises to optimize equipment efficiency, provide evaluation methods for the operation efficiency assessment of plant protection unmanned aircraft, provide reference for the selection of plant protection unmanned aircraft, and also provide basis for field planning.